O caráter destrutivo e a estética da barbárie em Walter Benjamin - Silva, Sérgio Paulo Barreto da (2018)
The present work aims to investigate the destructive and aesthetic ideas of barbarism in the work of Walter Benjamin. The concept of destruction, in Benjamin's thought, becomes broad inasmuch as all constructive action presupposes a destructive action. The destruction of the false appearance pervades both the historicist tradition and the cultural heritage. If the dialectical historian removes the ruins to make the paths visible, the avant-garde movements become barbaric, driven by a reaction to the process of domination of the cultural heritage. In this sense, the "crisis of tradition" in Benjamin's thinking is evident. Divided into two parts, the research will analyze, in the first part, the Benjaminian concept of destruction, showing historical-philosophical and cultural aspects and, in the second part, analyze the idea of an aesthetics of barbarism, with reference to the artistic vanguards, the new means of technical reproduction and the reaction of tradition from the aestheticization of politics.